A Biographical Compendium of Organic Name Reactions - Dieringer, Rachael K.; Lewis, David E. (My University, 2018)
Name reactions are a mainstay of organic chemistry, and serve as a useful shorthand in discussions among organic chemists. These discussions usually focus on the reaction itself, and seldom include any significant consideration of the chemist(s) who discovered or developed the reactions. We have begun the development of a biographical compilation of organic reactions, where the chemists are an important focus of the work. Our first chemist profiled is Arthur Michael (1853-1942) and his Michael Addition Reaction.
Color poster with text, images, and, photographs.
Keywords: Michael Addition Reaction; Michael, Arthur (1853-1942); Organic chemistry; Posters